1993
DOI: 10.1128/aem.59.1.156-162.1993
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the afl-2 gene involved in aflatoxin biosynthesis from Aspergillus flavus

Abstract: Aflatoxins are extremely potent carcinogens produced by AspergiUus flavus and AspergiUlus parasiticus. Cloning of genes in the aflatoxin pathway provides a specific approach to understanding the regulation of aflatoxin biosynthesis and, subsequently, to the control of aflatoxin contamination of food and feed. This paper reports the isolation of a gene involved in aflatoxin biosynthesis by complementation of an aflatoxinnonproducing mutant with a wild-type genomic cosmid library ofA. flavus. Strain 650-33, bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(116 citation statements)
references
References 28 publications
(30 reference statements)
4
111
0
1
Order By: Relevance
“…The gene was isolated from A. £avus by complementation in a mutant that did not produce a£atoxin and failed to convert exogenously supplied pathway intermediates to AFB1 [26,41]. In A. parasiticus, a£R was discovered when investigators observed increased metabolite production in an OMST-accumulating strain transformed with a cosmid containing a large DNA fragment from the a£atoxin gene cluster [42].…”
Section: Gene Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The gene was isolated from A. £avus by complementation in a mutant that did not produce a£atoxin and failed to convert exogenously supplied pathway intermediates to AFB1 [26,41]. In A. parasiticus, a£R was discovered when investigators observed increased metabolite production in an OMST-accumulating strain transformed with a cosmid containing a large DNA fragment from the a£atoxin gene cluster [42].…”
Section: Gene Regulationmentioning
confidence: 99%
“…£avus and A. parasiticus, an intact a£atoxin gene cluster is not required for a£atoxin production. Ectopic genomic integration of wild-type genes (both structural genes and A£R) into various mutants results in complementation of the mutated genes with no measurable e¡ects on gene expression [10,15,41]. Further, there is little evidence to indicate that gene order within the a£atoxin cluster in£uences regulation.…”
Section: Gene Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies on aflatoxin biosynthesis in A. flavus and A. parasiticus led to the cloning of 25 clustered genes within a 70 kb DNA region responsible for the enzymatic conversions in the aflatoxin biosynthetic pathway [8,9]. Regulatory elements such as aflR [10,11] and aflS (aflJ) [12,13], nutritional and environmental factors [14,15], fungal developmental and sporulation [16][17][18][19] were also found to affect aflatoxin formation. In A. flavus there are eight chromosomes with an estimated genome size of about 33-36 Mbp that harbor an estimated 12,000 functional genes (reviewed in [7,20], Dr. Machida, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…Fungi exist in every natural and man-made habitat in indoor and outdoor environments. Some molds, such as Aspergillus, Penicillium and Fusarium, produce a variety of allergenic substances, odorous chemicals and toxic metabolites (mycotoxins) [1][2][3][4]. The mycotoxins can cling to the surface of mold spores or be found within spores or on the growth substances.…”
Section: Introductionmentioning
confidence: 99%